A comparison of continuous femoral nerve block versus continuous epidural analgesia for analgesia in elderly patients with hip fractures - Temelkovska Stevanovska, Marina; Popovska, Snezhana (World Academy of Science, Engineering and Technology, 2020)
Uncontrolled acute pain and stress of surgery in elderly patients may cause increased cardiac morbidity and mortality. Early administration of central or peripheral block reduces the incidence of myocardial ischemia and dysrhythmias and the response to stress. The aim of this study was to compare the effect of continuous central and peripheral blocks on the incidence of cardiac complications and their analgesic effect in patients with high cardiac risk with hip fracture.
Keywords: epidural analgesia; femoral nerve block; perioperative cardiac risk; elderly; hip fracture